Enrichment of HER2 Amplification in Brain Metastases from Primary Gastrointestinal Malignancies. (29th October 2018) - Mitra, Devarati; Clark, Jeffrey W.; Shih, Helen A.; Oh, Kevin S.; Brastianos, Priscilla K.; Wo, Jennifer Y.; Strickland, Matthew R.; Curry, William T.; Parikh, Aparna R.; Corcoran, Ryan B.; Ryan, David P.; Iafrate, A. John; et al.
Abstract: Background: In nongastric gastrointestinal (GI) cancers, HER2‐positive (HER2+) disease is not common. In breast cancer, HER2 status is associated with increased risk of brain metastases and response to HER2‐targeted therapy. The purpose of this project was to compare HER2 status in GI cancer brain metastases versus matched prior sites of disease in order to determine if HER2+ disease is more common intracranially. Materials and Methods: We identified 28 patients with GI cancer who had craniotomy for brain metastases between 1999 and 2017 with intracranial metastatic tissue available at Massachusetts General Hospital. Twenty‐four patients also had tissue from a prior site of disease. Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) for HER2 were performed on all samples. A tumor was defined as HER2+ if it had 3+ staining by IHC or amplification by FISH. Results: A prior site of disease (including intracranial metastases) was HER2+ for 13% of evaluable patients: 3 of 11 patients with colorectal cancer and no patients with esophageal or pancreatic cancer. The most recent brain metastases were HER2+ for 32% of patients: 2 of 3 esophageal squamous cell carcinomas, 3 of 10 esophageal adenocarcinomas (ACs), 3 of 14 colorectal ACs, and 1 of 1 pancreatic AC. Only 37.5% of patients with HER2+ brain metastasis had concordant HER2+ prior tissue (κ = 0.38, p = .017). Conclusion: In this cohort of patients with GI cancer with brain metastases, HER2+ status was more common intracranially compared with prior sites of disease. These findings suggest that testing HER2 in patients with GI cancer with brain metastases may lead to additional therapeutic options, regardless of HER2 status in previously examined tissue. Implications for Practice: HER2 amplification is a well‐known driver of oncogenesis in breast cancer, with associated increased risk of brain metastases and response to HER2‐directed therapy. In nongastric gastrointestinal (GI) cancers, HER2 amplification is not common and consequently is infrequently tested. The current study shows that brain metastases in patients with GI primary malignancies have a relatively high likelihood of being HER2 positive despite HER2 amplification or overexpression being less commonly found in matched tissue from prior sites of disease. This suggests that regardless of prior molecular testing, patients with GI cancer with brain metastases who have tissue available are likely to benefit from HER2 assessment to identify potential novel therapeutic options. Abstract : This article presents results of a study comparing HER2 status in tissue from matched brain metastases and a prior site of disease from patients with gastrointestinal primary malignancies to determine if HER2+ disease is more common intracranially.